การพัฒนาเมืองเชียงรายเพื่อรองรับการคมนาคมขนส่งทางรถไฟ - เกริก กิตติคุณ (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
To study factors and changes of Chiang Rai town in relating to the train transportation in 2009, and to recommend guidelines for the town s development. The study process comprises the secondary data obtained from physical, economic, social and population of Chiang Rai town and collect primary data from field survey on existing conditions, land use and the feasibility study of Den Chai to Chiang Rai Railway Project which estimated passengers and freight forecasts. Those data have been analyzed the factors and changes which related to the train transportation. Finally, the development guidelines for Chiang Rai town is presented. The thesis found that the economic changes to activities of trade and services in railway station area are from commuters including tourists and local passengers, and activities of container deport in surrounding areas are from freight transportation. The land use around the station area will be changed to commercial use, while land use in surrounding areas will be changed to industrial use and warehouses storing goods, agricultural products, cement and petroleum container. The considering factors and changes of Chiang Rai town are used to recommend guidelines to land use and infrastructure development relating to the train transportation of Chiang Rai town.